Exploration and Practice of Integrating Excellent Chinese Traditional Culture into Primary School English Teaching - Kang, Tianqi (International Journal of Social Sciences and Public Administration, 2025)
In an era of increasing globalization and cultural exchange, integrating traditional Chinese culture into primary school English teaching not only promotes students’ English proficiency but also enhances their cultural identity and intercultural competence. This paper explores the theoretical foundation, pedagogical significance, and practical strategies for incorporating elements of traditional Chinese culture into English language education at the primary school level. Drawing on relevant theories such as intercultural communicative competence, constructivism, and culturally responsive teaching, this study analyzes case examples, classroom designs, and empirical feedback from practicing teachers. The findings indicate that embedding Chinese cultural content-such as festivals, idioms, moral stories, and art forms-within English lessons fosters student engagement, enriches content learning, and nurtures cultural pride. Finally, this paper proposes a pedagogical model and offers suggestions for effective integration that align with current curriculum standards and international perspectives.